(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the level of health literacy (HL) and the profile in patients with chronic diseases. Methodology: This is an observational, cross-sectional study that used the Brazilian adaptation of the Test of Functional Health Literacy in Adults (S-TOFHLA). Clinical and epidemiological data were also collected. The interviews took place from September to November of 2021. Results: Seventy patients were interviewed, half had an adequate level by the S-TOFHLA, while 27.1% had a limited level and 22.9% had an inadequate level. In the sample, women predominated (70%), mean age of 56.3 ± 10.6, 60% married, 48.6% self-declared white and more half with an educational level above high school. In the group with a level of limited/inadequate literacy, there were more men (42.9% vs. 17.1%) and older age (60.7 ± 8.5 vs. 51.8 ±10.8 years). Systolic blood pressure (144.4 ± 14.9 vs. 128.2 ± 13.5 mmHg) and random blood glucose levels (175.3 ± 55.9 vs. 126.4 ± 45.4 mg/dL) were also higher in this group. Conclusion: Half of the patients had limited/inadequate health literacy, with a predominance of men and advanced age. These findings of poorer literacy were associated with a trend towards worse control of parameters related to chronic diseases and a greater need of medications.